2017
DOI: 10.1002/14651858.cd012815
|View full text |Cite
|
Sign up to set email alerts
|

Marine-derived n-3 fatty acids therapy for stroke

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of marine-derived n-3 fatty acids administration on functional outcomes and dependence in people with stroke. 1 Marine-derived n-3 fatty acids therapy for stroke (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Bempedoic acid is a first-in class therapy adenosine triphosphate-citrate lyase 54 inhibitor that reduces LDL-C levels by 15% to 25% depending on the type and dose of background statin therapy and is associated with fewer muscle-related adverse effects. 33,34 It is also available in a combination product with ezetimibe that reduces LDL-C levels by ∼35%.…”
Section: Treatmentmentioning
confidence: 99%
“…Bempedoic acid is a first-in class therapy adenosine triphosphate-citrate lyase 54 inhibitor that reduces LDL-C levels by 15% to 25% depending on the type and dose of background statin therapy and is associated with fewer muscle-related adverse effects. 33,34 It is also available in a combination product with ezetimibe that reduces LDL-C levels by ∼35%.…”
Section: Treatmentmentioning
confidence: 99%
“…Some metabolites have been reported to play a critical role in the development of cardiac hypertrophy and heart failure by regulating inflammatory reaction [19][20][21] . Recently, clinical trials showed that omega-3 FA supplementation reduced cardiovascular events [22][23][24][25][26] , but the underlying molecular mechanisms remain unknown.…”
mentioning
confidence: 99%
“…The Supplementation en Folates et Omega‐3 trial found no effect of post‐stroke supplementation with 600 mg eicosapentaenoic and docosahexaenoic acids (2:1 ratio) on health‐related quality of life, measured by the Medical Outcomes Study 36‐Item Short‐Form Health Survey [30]. Two small studies observed non‐significant protective effects of n‐3 fatty acid supplementation on functional outcomes, as measured by the GOSE scale, the Barthel Index, and the Rivermead Mobility Index [31,32], although the quality of the evidence from these studies was judged to be of very low in a recent Cochrane review [33]. In addition, these studies only assessed post‐stroke supplementation with n‐3 fatty acids and could not assess how supplementation prior to the event may influence outcomes.…”
Section: Discussionmentioning
confidence: 99%